On the transformation of organic components of technogenic outflows in lithospheric reactors - A D Gladush (RUDN Journal of Engineering Research, 2008)
In the article possibility of earth reactors a technogeneous of reproduction hydrocarbon resources with an aim utilization hydrocarbon waste has been analyzed.